PELATIHAN PELAKSANAAN K3 DALAM PENGGUNAAN ALAT PEMADAM API DAN PENCEGAHAN KEBAKARAN DI LINGKUNGAN PERUSAHAAN - Komarudin, Mamay; Tabroni, Tabroni; Afiah, Efi Tajuroh (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The Company that is the site of many activities several times experienced fires. Some companies have even experienced fires twice in the past 12 months. One of the causes of the fire is an electrical short circuit. Poor employee knowledge and lack of understanding related to fire anticipation are among the factors in the occurrence of fires in the Company. Therefore, it is necessary to conduct K3 implementation training activities, in this case, the use of Fire Extinguishers and kill the fire in ways other than using extinguishers. The training method is by way of direct practice, then excellent and correct application. The hope is that the training results are that employees can understand the standard procedures and understand the dangers posed by fire that are not immediately extinguished so that this activity can minimize the occurrence of fires in the Company